Estratégias Tradutológias para Tradução de Alusões: exemplos de aplicabilidade - Tecchio, Iliane (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article presents a study about translation strategies to the translation of allusions. First, it is taken the issue of intertextuality and allusion as intertextual references. In the sequence, it is presented the translation strategies for translation of allusions suggested by Ritva Leppihalme (1997) and it is illustrated their applicability in the translation of religious allusions selected from the book Dracula (1897) of the Irish writer Bram Stoker. The study showed that, for both, the beginner and the experienced translator, the theoretical knowledge of translation studies can assist in the transposition of certain intertextual elements, contributing, therefore, to avoid a cultural impact and, by extension, support the reader in a deeper understanding of the work.